2022
DOI: 10.1038/s41467-022-30582-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutational signatures are markers of drug sensitivity of cancer cells

Abstract: Genomic analyses have revealed mutational footprints associated with DNA maintenance gone awry, or with mutagen exposures. Because cancer therapeutics often target DNA synthesis or repair, we asked if mutational signatures make useful markers of drug sensitivity. We detect mutational signatures in cancer cell line exomes (where matched healthy tissues are not available) by adjusting for the confounding germline mutation spectra across ancestries. We identify robust associations between various mutational signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 107 publications
(158 reference statements)
1
30
0
Order By: Relevance
“…gdc.cancer.gov/] (dbGaP accession ID phs000178) and processed as described in ref. 113 . Copy numbers were identified with the tool FACETS 114 .…”
Section: Extraction Of Somatic Mutational Features and Somatic Compon...mentioning
confidence: 99%
“…gdc.cancer.gov/] (dbGaP accession ID phs000178) and processed as described in ref. 113 . Copy numbers were identified with the tool FACETS 114 .…”
Section: Extraction Of Somatic Mutational Features and Somatic Compon...mentioning
confidence: 99%
“…Our analyses revealed that only COSMIC signatures SBS18 and SBS36 (SBS18/36), both previously attributed to reactive oxygen species 61,62 , were found to be operative in all irradiated MEF and HFF cells. It should be noted that ROS signatures SBS18 and SBS36 have cosine similarity of 0.914 ( Figure 7 a ), which, in many cases, makes them hard to distinguish from one another and these signatures are commonly reported together as SBS18/36 35,63,64 . Our analyses revealed that SBS18/36 were the only signatures enriched in irradiated HFF and MEF samples when compared to controls ( Figure 7 b-c ; q-values<0.05; Mann-Whitney tests).…”
Section: Resultsmentioning
confidence: 99%
“…their mutational consequences such as microsatellite expansion) might turn out to be a more robust therapeutic approach than targeting the primary DDR defect itself, given it is difficult to understand how the mutational consequences of many DDR defects could be easily reversed. Whilst this might be theoretically possible with WRN inhibitors in cancers with expanded TA repeats, approaches that target cancers with different types of mutational signature are not known but could be identified (an attempt to identify these is described here [172]). For example, in experimental models, though a BRCA2 reversion is able to restore HR and cause PARPi resistance, it does not restore a normal diploid genome to tumour cells; PARPi‐resistant BRCA2 ‐revertant cells retain a highly disordered genome and are still p53 mutant [173].…”
Section: Targeting Ddr Inhibitor Resistancementioning
confidence: 99%